The Impact of Sheath Size in Miniaturized Percutaneous Nephrolithotomy in Adult Patients; A Matched-pair Analysis - Erbin, Akif; Ucpinar, Burak; Cubuk, Alkan; Yazici, Ozgur; Uysal, Harun; Savun, Metin; Basal, Seref; Akbulut, Mehmet Fatih (Urology Journal, 2019)
Purpose: The miniaturized percutaneous nephrolithotomy (mPNL) can be performed by using a very wide range of different access sheaths (14-22 Fr).It has been well known that tract size is one of the main parameters affecting the complication rates in PNL. We aimed to compare 21 Fr with 16.5 Fr mPNL tract sizes in adult patients. Material and Methods: From May 2013 to April 2018, 604 patients with kidney stone underwent mPNL in our department. The study was designed as retrospective and match-pair analysis was the preferred method for the formation of groups. The 21 Fr mPNL cases were matched with 16.5 Fr mPNL cases at a 1:1 ratio, according to the patients’ age, gender, body mass index, American Society of Anesthesiologists (ASA) score, stone characteristics (stone size, opacity and localization) and hydronephrosis. Patients with solitary kidney, renal anomalies, musculoskeletal abnormalities, and pediatric patients (< 18 years old) were excluded from the study. Both groups (21 Fr and 16.5 Fr) were compared in terms of demographics, stone characteristics, operative data and post-operative outcomes. Results: A total of 260 patients were included in the study (130; 21 Fr mPNL group and 130; 16.5 Fr mPNL group). The operation time was significantly shorter in 21 Fr group (21 Fr; 85.2±37.5, 16.5 Fr; 101.7±37.7 minutes, p: 0.001). Complete stone clearance rates were 76.9% and 62.3% in 21 Fr and 16.5 Fr mPNL, respectively (p: 0.01). There was no significant difference between the groups in terms of overall operative and post-operative complications. However, in subgroups analysis, post-operative fever was higher in 16,5 Fr mPNL (4 patients in 16.5 Fr, no patients in 21 Fr group, p: 0.044); steinstrasse, renal colic and post-operative JJ stent requirement rates were higher in 21 Fr mPNL procedure (p: 0.018, p: 0.031 and p: 0.046, respectively). The hospitalization time was significantly higher in 21 Fr (p: 0.01). Conclusions: Although 21 Fr mPNL procedure has advantages such as better success rates and shorter operation time, some post-operative complications (steinstrasse, renal colic, post-operative JJ stent requirement) are against of 21 Fr mPNL when compared with 16.5 Fr mPNL procedure. Further randomized prospective studies with larger patient volume are needed to confirm these results.